<h3>
Answer: x(x+1)(5x+9) </h3>
===================================================
Work Shown:
5x^3 + 14x^2 + 9x
x( 5x^2 + 14x + 9 )
To factor 5x^2 + 14x + 9, we could use the AC method and guess and check our way to getting the correct result.
A better way in my opinion is to solve 5x^2 + 14x + 9 = 0 through the quadratic formula
Then use those two solutions to find the factorization
x = -1 or x = -9/5
x+1 = 0 or 5x = -9
x+1 = 0 or 5x+9 = 0
(x+1)(5x+9) = 0
So we have shown that 5x^2 + 14x + 9 factors to (x+1)(5x+9)
-----------
Overall,
5x^3 + 14x^2 + 9x
factors to
x(x+1)(5x+9)
Answer:
corresponding
Step-by-step explanation:
Answer:
Use the formula change in y divided by change in x to get your answer
Answer:
Step-by-step explanation:
(-2 + x)/2= 4
-2 + x = 8
x = 10
(2 + y)/2 = -3
2 + y = -6
y = -8
(10, -8) for endpoint H
0.9090909.../2
This is the equivalent and it has no equal fraction counterpart